Pengembangan Media Pembelajaran Modul Interaktif Menggunakan Lectora Inspire Pada Mata Pelajaran Simulasi Dan Komunikasi Digital - Yenni anty; Zainuddin Untu; Dydik Kurniawan (PROCEEDING UMSURABAYA, 2021)
Abstract: This study aims to develop and determine the feasibility of learning media for desktop-based interactive modules on digital citizenship material at SMK TI Airlangga Samarinda for the 2020/2021 academic year. The type of research used is Research and Development (R&D). The results of this study are: 1) Development of desktop-based Interactive Module learning media on Simulation and Digital Communication subjects with theapplication Lectora Inspire. 2) The feasibility test can be seen in the questionnaire results obtained from three media experts with 23 indicators, the total score is 268 out of a maximum score of 345 with the category "Feasible", the percentage of feasibility is 77.68%. Testing by material experts with 10 indicators obtained a total score of 43 out of a maximum score of 50 in the category "Very Appropriate" with a percentage of 86% feasibility. Testing of five media users with 15 indicators obtained a total score of 310 from a maximum score of 375 in the category "Very Appropriate" with a percentage of 82.67% feasibility. Based on this description, it can be concluded that the desktop-based interactive learning media with the Lectora Inspire developed is suitable for use in Simulation and Digital Communication learning on Digital Citizenship material.Â Keywords:Â  Interactive Learning Media, Lectora Inspire